"Síndrome de Burnout em professores de ensino especial" - Braun, Ana Claudia (2012)
This dissertation consists of two articles that investigate Burnout Syndrome (BS) in special education teachers. The first, Burnout Syndrome in Special Education teachers , aims to study the prevalence of Burnout Syndrome and its association with sociodemographic and labor variables and occupational coping strategies in the population of special education teachers in the region of Vale dos Sinos. The second article, Burnout Syndrome: a comparative study of special education and regular teachers , aims to determine whether there is a difference in the rates of the dimensions of BS between special and regular education. The study in the first article involved 88 teachers that work in special education schools. As research tools, we used a questionnaire to record sociodemographic and labor variables, the Cuestionario para la Evaluación del Síndrome de Quermarse por el Trabajo (CESQT) for the evaluation of BS, and the Occupational Coping Scale to assess occupational coping strategies. The results demonstrate a positive association between the number of weekly work hours in teaching and the dimension of Enthusiasm toward the job.The number of students served was negatively correlated with the dimension of Guilt. In relation to coping strategies, the use of control strategies revealed a positive association with Enthusiasm toward the job and the use of avoidance strategies associated negatively with Enthusiasm toward the job and positively with Psychological exhaustion and Indolence. The second article examined two groups from two databases. Group 1 consisted of 80 special education teachers and Group 2 of 80 regular education teachers. The research instruments used for The evaluation of BS were the Cuestionario para la Evaluación del Síndrome de Quemarse por el Trabajo (CESQT) and a sociodemographic and labor data questionnaire. Results evidence differences in the dimension of Enthusiasm toward the job, as well as Profiles 1 and 2 of BS among the groups of special education and regular teachers. Results indicate that special education teachers have less potential risk of developing burnout, probably due to the greater sense of enthusiasm at work, measured by the dimension of Enthusiasm toward the job. Both articles intended to subsidize new studies and designs in order to establish promotion and prevention of BS in special education teachers benefiting students, schools and school community.